Impacts of Model Bias on the Climate Change Signal and Effects of Weighted Ensembles of Regional Climate Model Simulations: A Case Study over Southern Québec, Canada - Eum, Hyung-Il; Gachon, Philippe; Laprise, René (Advances in Meteorology, 2016)
This study examined the impact of model biases on climate change signals for daily precipitation and for minimum and maximum temperatures. Through the use of multiple climate scenarios from 12 regional climate model simulations, the ensemble mean, and three synthetic simulations generated by a weighting procedure, we investigated intermodel seasonal climate change signals between current and future periods, for both median and extreme precipitation/temperature values. A significant dependence of seasonal climate change signals on the model biases over southern Québec in Canada was detected for temperatures, but not for precipitation. This suggests that the regional temperature change signal is affected by local processes. Seasonally, model bias affects future mean and extreme values in winter and summer. In addition, potentially large increases in future extremes of temperature and precipitation values were projected. For three synthetic scenarios, systematically less bias and a narrow range of mean change for all variables were projected compared to those of climate model simulations. In addition, synthetic scenarios were found to better capture the spatial variability of extreme cold temperatures than the ensemble mean scenario. These results indicate that the synthetic scenarios have greater potential to reduce the uncertainty of future climate projections and capture the spatial variability of extreme climate events.
Keywords: Gachon_Philippe

Inondations des printemps 2017 et 2019 dans le bassin versant de la rivière des Outaouais (Québec, Canada) : analyse des facteurs physiographiques et météorologiques en cause - Benoit, Clémence; Demers, Isabelle; Roberge, François; Gachon, Philippe; Laprise, René (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Gachon_Philippe